2007
DOI: 10.1073/pnas.0707417104
|View full text |Cite
|
Sign up to set email alerts
|

The second Ca 2+ -binding domain of the Na + –Ca 2+ exchanger is essential for regulation: Crystal structures and mutational analysis

Abstract: The Na ؉ -Ca 2؉ exchanger plays a central role in cardiac contractility by maintaining Ca 2؉ homeostasis. Two Ca 2؉ -binding domains, CBD1 and CBD2, located in a large intracellular loop, regulate activity of the exchanger. Ca 2؉ binding to these regulatory domains activates the transport of Ca 2؉ across the plasma membrane. Previously, we solved the structure of CBD1, revealing four Ca 2؉ ions arranged in a tight planar cluster. Here, we present structures of CBD2 in the Ca 2؉ -bound (1.7-Å resolution) and -f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
0
11

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(148 citation statements)
references
References 33 publications
2
135
0
11
Order By: Relevance
“…Structural studies clearly demonstrated that CBD domains do not undergo significant conformational changes upon Ca 2ϩ binding (7)(8)(9), although some specific (yet unidentified) electrostatic interactions of Ca 2ϩ with CBD sites may drive functionally important reorientation of two CBD domains (17,26,(33)(34)(35) sites of CBD1 are separated by 3-4 Å) and exhibit positive cooperativity for Ca 2ϩ binding despite the strong charge repulsion between the adjacent divalent cations (16,17,25,26,(33)(34)(35). The close adjacencies of Ca 2ϩ sites in CBDs (7)(8)(9)33) is consistent with a sharp dependence of Ca 2ϩ binding on pH (36 -38). The binding of the first Ca 2ϩ ion to CBD may partially (or fully) deprotonate the coordinating residue(s), thereby enabling the next Ca 2ϩ ion to bind to the remaining site(s).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural studies clearly demonstrated that CBD domains do not undergo significant conformational changes upon Ca 2ϩ binding (7)(8)(9), although some specific (yet unidentified) electrostatic interactions of Ca 2ϩ with CBD sites may drive functionally important reorientation of two CBD domains (17,26,(33)(34)(35) sites of CBD1 are separated by 3-4 Å) and exhibit positive cooperativity for Ca 2ϩ binding despite the strong charge repulsion between the adjacent divalent cations (16,17,25,26,(33)(34)(35). The close adjacencies of Ca 2ϩ sites in CBDs (7)(8)(9)33) is consistent with a sharp dependence of Ca 2ϩ binding on pH (36 -38). The binding of the first Ca 2ϩ ion to CBD may partially (or fully) deprotonate the coordinating residue(s), thereby enabling the next Ca 2ϩ ion to bind to the remaining site(s).…”
Section: Discussionmentioning
confidence: 99%
“…Extreme Cooperativity of Ca 2ϩ -dependent Activation of I NCX in Ventricular Myocytes-A Hill coefficient of n H ϭ 2-3 has been reported for the Ca 2ϩ -dependent activation of I NCX in giant patches of cardiomyocytes and in oocyte expression systems (6,8,26,27). This cooperativity of the allosteric activation of NCX1 by Ca 2ϩ is consistent with the involvement of three Ca 2ϩ sites (among the six sites on the CBD12 tandem region) that regulate NCX1 (25,26 45 Ca binding to isolated CBDs (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two high affinity (K d Ͻ 0.3 M) sites of CBD1 (Ca3 and Ca4) serve as the primary Ca 2ϩ sensor (7). A medium affinity site (CaI with a K d of 2-10 M) enables sustained NCX activation while also relieving Na ϩ -dependent inactivation (5,7,8). The site CaII of CBD2 serves as the Mg 2ϩ binding site (9,10), whereas the role of low affinity (K d Ͼ 10 M) sites of CBD1 (Ca1 and Ca2) remains unclear (7).…”
Section: Mammalian Namentioning
confidence: 99%
“…2). Further rise in cytosolic Ca 2ϩ may result in occupation of the CaI site at CBD2, alleviating Na ϩ -dependent inactivation and thus, allowing sustained NCX activation (5,8 …”
Section: Role Of the Low Affinity Ca1-ca2mentioning
confidence: 99%